Improving Early Childhood Speaking Skills through the Use of Character Puppet Media: An Experimental Study on Children Aged 4-5 Years - Eka Prasetiawati (Jurnal Jendela Bunda Program Studi PG-PAUD Universitas Muhammadiyah Cirebon, 2025)
This study aims to examine the speaking abilities of children aged 4–5 years at TK IT Noor Hidayah and to evaluate the effectiveness of the storytelling method using character puppet media in enhancing their speaking skills. The research focuses on three main objectives: (1) to describe the initial speaking ability of the children before the implementation of the storytelling method, (2) to analyze the process of implementing the storytelling method using character puppet media as a learning strategy, and (3) to evaluate the outcomes of children's speaking ability after the application of the method. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings reveal that prior to the intervention, the children’s speaking skills were relatively low, especially in vocabulary, speaking confidence, and sentence structure. The use of character puppet storytelling increased children's enthusiasm, participation, and verbal expression. Character puppet media proved to be an effective and engaging teaching aid that stimulated the development of children's speaking abilities. Therefore, this method is recommended as an alternative language learning strategy for early childhood education.